If 3m = 5m -3/5, then m = ?
Answers
Answered by
1
Answer:
0.3
Step-by-step explanation:
3m = 5m - 3/5
3/5 = 5m - 3m
3/5 = 2m
m = 3 / 5 multiplied by 2
m = 3/10
m = 0.3
Answered by
1
Answer:
0.3
Step-by-step explanation:
I THINK IT MAY HELP YOU GUYS PLEASE MARK ME AS BRILLIANT AS SOON AS POSSIBLE
Attachments:
![](https://hi-static.z-dn.net/files/ddf/804dc563e963cfb19c9c6c4f2907271e.jpg)
Similar questions
Accountancy,
2 months ago
Math,
2 months ago
History,
2 months ago
Math,
4 months ago
Computer Science,
4 months ago
English,
11 months ago